Geopolitics in the Baltic Sea region : the "Zeitenwende" in the context of critical maritime infrastructure, escalation threats and the German willingness to lead - Swistek, Göran; Paul, Michael (2023)
Zusammenfassung: Due to its strategic immensity and opportunities for covert action, the maritime domain has become the most prominent arena of modern-day great power rivalry. In the shadow of this confrontation and the Russian war of aggression against Ukraine, the Baltic Sea is now the focus of geopolitical interest and conflict. An expression of this is the increase in hybrid activities, from acts of sabotage to the use of unidentified drones. For the Western states of the Baltic Sea region in particular, all of this highlights their dependence on fossil resources, critical maritime infrastructure, and secure trade routes. In response to the war against Ukraine and Russian naval activity in the Baltic Sea, littoral states have placed their militaries on heightened readiness. In the midst of this crisis situation, NATO allies and future allies remain locked in an unnecessary dispute over force dispositions, new structures and leadership roles. As a result, there is little sign of the German "Zeitenwende" in the Baltic Sea region